Analisis Kelayakan Investasi Truk Menggunakan Net Present Value, Payback Period, dan Internal Rate of Return pada PT Swisstex Naratama Indonesia - Ridwan Margana, Riki; Kusumah, Okky (Journal of Technology and Engineering, 2024)
PT Swisstex Naratama Indonesia is a private company engaged in the sale or distribution of chemicals for textiles. The problem with PT Swisstex Naratama Indonesia is that it lacks a fleet of trucks to send products from the central warehouse to the warehouse in Solo City, so the company carries out the delivery process using the CV XYZ delivery service. Due to an increase in rental rates of 15% every year, PT Swisstex Naratama Indonesia plans to buy 1 unit of a new truck to overcome this problem but there is a rejection of the request which makes the company have to evaluate whether the investment in purchasing 1 unit of truck is feasible or not. The shipping demand data used is data for 2020-2022, demand for the next 5 years is analyzed using the forecasting decomposition method. The methods used to analyze investment feasibility are Net Present Value, Payback Period, and Internal Rate of Return. The NPV obtained from purchasing a truck is – IDR 1,188,596,987 and the NPV for renting a truck is – IDR 1,464,905,648. Based on Payback Period calculations, the company needs 4 years and 6 months to return the initial capital from its investment. This time is shorter than the economic fleet's lifespan, which is 5 years. And based on the results of truck investment calculations, an IRR value of 16.21% was obtained. When compared with the required profit level of 15%, the IRR value from the calculation results is higher. By considering the NPV criteria, PP and IRR assessments, it can be concluded that investment in purchasing a fleet of Mitsubishi brand trucks, Colt Diesel Double FE 73 110 PS, can be implemented or is considered feasible.